Case Report: 65 Year Old Woman with Cerebellopontine Angle Tumor: Laporan Kasus : Wanita 65 tahun dengan Tumor Cerebellopontine Angle - Yasmin, Nabila Rayhan (Jurnal Agromedicine Unila: Jurnal Kesehatan dan Agromedicine, 2024)
Cerebellopontine angle (CPA) tumor is the most common neoplasm in the posterior fossa. Most CPA tumors are benign and slow growing. The most common type of CPA tumor is vestibular schwannoma. A 65 year old woman was brought to the emergency room with a sudden loss of consciousness during activities 5 hours before entering the hospital. There are complaints of seizures and vomiting. Complaints of headaches are getting worse over time, feeling like pressure, moderate to severe intensity. The patient has difficulty maintaining balance and often falls. There has been hearing loss since 15 years ago. On physical examination, there was interference with nerve VIII, left auricular sensorineural deafness. On the CT scan, a mixed mass appeared in the left cerebellopontine angle. Patients were diagnosed with CPA tumors based on clinical findings and imaging examination. Patients receive therapy and observe tumor growth.